An epidemic of abuse and violence: Nurse on the front line - Chapman, Rose; Styles, I. (Elsevier Ltd, 2006)
This commentary paper highlights the every day reality for nurses facing episodes of violence and aggression while working in the health care system in Western Australia and identifies future research necessary to address the problem. Nurses, in a range of work environments, face the terrifying possibility of being victims of aggressive and violent incidents while caring for patients. The consequences of these events are far reaching and include an increased cost to the health care system, loss of experienced nurses from the workforce and the inability to attract nurses back to the bedside. Although the West Australian government has attempted to address the problems with quick fixes, no current initiatives have been effective and nurses are still experiencing assault in ever increasing numbers. To ensure that nurses stop being the victims of these events it is essential that nurses, government and the community refuse to accept that violence and aggression are 'just part of the job'. Sound research is important in raising awareness and providing direction for hospital policy and practice. Furthermore, future research in the area has to investigate the phenomenon as a whole taking into consideration all aspects of these events. The results of this research must then form the framework for future education programs, policies and best-practice guidelines for safety of nurses and ultimately patient care.